Pengakuan, Akumulasi, dan Tanah Adat dalam Kapitalisme Hijau: Studi Perbandingan Indonesia, Filipina, dan Selandia Baru - Virtuous Setyaka; Fajri Rahman (Andalas Journal of International Studies (AJIS), 2025)
This article examines why legal recognition of Indigenous land rights has expanded globally while material control over land and resources remains constrained. Drawing on a comparative analysis of Indonesia, the Philippines, and Aotearoa New Zealand, the study analyzes how international Indigenous rights norms—particularly UNDRIP and related international standards often associated with ILO Convention No. 169—are domesticated through distinct configurations of state authority, market integration, and legal pluralism. Using an interpretive comparative policy analysis of legal texts, policy documents, judicial decisions, and multilateral reports (2010–2024), the article shows that recognition reforms increasingly operate as instruments for regulating Indigenous territories within green developmental and market-oriented governance frameworks. While legal recognition expands formally, it simultaneously re-scales Indigenous authority into administrative and market-compatible forms. Conceptually, the article advances the notion of accumulation through recognition to capture a specific mechanism through which legal acknowledgment of Indigenous land rights enables new forms of assetization, investment eligibility, and ecological commodification without substantive redistribution of territorial sovereignty. This finding contributes to debates in agrarian political economy and critical international political economy by showing how rights-based reforms can become embedded within contemporary regimes of green capitalism.